THE EFFECTIVENESS OF USING SOCIAL MEDIA YOUTUBE IN IMPROVING THE SPEAKING SKILL OF THE FIRST GRADE STUDENTS OF SMA NEGERI 2 GOWA - Gifari, Nursyamri; Muliati, Andi; Talib, Ahmad (State University of Makassar, 2022)
The objective of this research was to find out whether the use of social media YouTube is effective in improving the speaking skill of the first-grade students of SMA Negeri 2 Gowa. This research took place at SMA Negeri 2 Gowa. The population of this research was the students of SMA Negeri 2 Gowa. The researcher used purposive sampling technique. The instrument of this research was a speaking test which was administered as a pre-test and post- test. Based on the result of the mean score, the researcher found that the use of social media YouTube can improve students speaking abilities. It was proved by the result of the post-test which was higher than result of the pre-test (29.11 > 46.06). Furthermore, the researcher concluded that the use of social media YouTube effective in improving the speaking skill of the first-grade students of SMA Negeri 2 Gowa. Keywords— improving, social media YouTube, speaking skill